Władczy oraz negocjacyjny typ tworzenia prawa. Szanse i zagrożenia - Kustra, Ewa (Wydział Prawa i Administracji UAM, 1994)
The paper begins with a distinction between the autocratic and negotiating type of the legal system and related to it autocratic or negotiating type of the law making. The two types served as models and have been described by referring them to the concept of the law-making programme. An autocratic type is seen as having goal-oriented programmes, whereas the negotiating type seems to be based on conditioning and procedural programmes. Advantages and disadvantages of each of the two models have been discussed and a possibility of instrumentalisation of the law in a given model considered. It has been emphasised that the negotiating manner of law-making does not always make it possible to overcome difficulties resulting from the autocratic type.
Autocratic and negotiating type of the law-making. Opportunities and threats